Experimental genital tract infection demonstrates Neisseria gonorrhoeae MtrCDE efflux pump is not required for in vivo human infection and identifies gonococcal colonization bottleneck. - Andreea Waltmann; Jacqueline T Balthazar; Afrin A Begum; Nancy Hua; Ann E Jerse; William M Shafer; Marcia M Hobbs; Joseph A Duncan (PLoS Pathogens, 2024)
The MtrCDE efflux pump of Neisseria gonorrhoeae exports a wide range of antimicrobial compounds that the gonococcus encounters at mucosal surfaces during colonization and infection and is a known gonococcal virulence factor. Here, we evaluate the role of this efflux pump system in strain FA1090 during in vivo human male urethral infection with N. gonorrhoeae using a controlled human infection model. With the strategy of competitive infections initiated with mixtures of wild-type FA1090 and an isogenic mutant FA1090 strain that does not contain a functional MtrCDE pump, we found that the presence of the efflux pump is not required for an infection to be established in the human male urethra. This finding contrasts with previous studies of in vivo infection in the lower genital tract of female mice, which demonstrated that mutant gonococci of a different strain (FA19) lacking a functional MtrCDE pump had a significantly reduced fitness compared to their wild-type parental FA19 strain. To determine if these conflicting results are due to strain or human vs. mouse differences, we conducted a series of systematic competitive infections in female mice with the same FA1090 strains as in humans, and with FA19 strains, including mutants that do not assemble a functional MtrCDE efflux pump. Our results indicate the fitness advantage provided by the MtrCDE efflux pump during infection of mice is strain dependent. Owing to the equal fitness of the two FA1090 strains in men, our experiments also demonstrated the presence of a colonization bottleneck of N. gonorrhoeae in the human male urethra, which may open a new area of inquiry into N. gonorrhoeae infection dynamics and control. TRIAL REGISTRATION. Clinicaltrials.gov NCT03840811.